Statistical techniques in business and economics - Mason, Robert D.; Lind, Douglas A.; Marchal, William G. (Boston, Mass. : Irwin/McGraw Hill, 1999)
It provides students in marketing, accounting, finance, international business, sales, management, and other fields of business and economics with sound introduction to descriptive and inferential statistics.
Previous ed.: 1996.
One computer laser disc (4 3/4 in.)
Includes bibliographical references and index.
uaj 05/05/2015; nmn16/6/15
Loan
Keywords: Social sciences - statistical methods; Economics - statistical methods; Commercial statistics - statistical methods